2020
DOI: 10.1159/000504228
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Contributed to Pulmonary Arterial Hypertension Development via Stimulating Aquaporin Expression and Pulmonary Arterial Smooth Muscle Cells Proliferation

Abstract: Introduction and Objective: The regulatory network of aquaporin (AQP) 1 and renin-angiotensin-aldosterone (ALDO) system are not quite clear in pulmonary arterial hypertension (PAH). Thus, we explored the role of AQP1, ALDO and spirolactone (SP) in the PAH animal model and pulmonary arterial smooth muscle cells (PASMCs). Method: PAH rat model was established by monocrotaline (MCT) via intraperitoneal in SD rat. Hemodynamic measurement was conducted via the external jugular vein cannula. PASMCs were extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In this context, AQP1 deficiency (null mice) showed increase in lung ischemia-reperfusion injury that was mediated via lowered stability of HIF-2α [154]. In a recent study, increased AQP1 expression was shown to play a role in aldosterone mediated development of pulmonary arterial hypertension [155] In acute lung injury (ALI), pre-B cell colony-enhancing factor (PBEF), which is involved in enhancing the inflammatory factors, downregulated AQP1 expression primarily via MAPK pathways [156]. Another study using rat pleural mesothelial cells showed role of p38 MAPK pathway in downregulation of AQP1 by Staphylococcus peptidoglycan [157].…”
Section: Transcriptional/translational Regulationmentioning
confidence: 99%
“…In this context, AQP1 deficiency (null mice) showed increase in lung ischemia-reperfusion injury that was mediated via lowered stability of HIF-2α [154]. In a recent study, increased AQP1 expression was shown to play a role in aldosterone mediated development of pulmonary arterial hypertension [155] In acute lung injury (ALI), pre-B cell colony-enhancing factor (PBEF), which is involved in enhancing the inflammatory factors, downregulated AQP1 expression primarily via MAPK pathways [156]. Another study using rat pleural mesothelial cells showed role of p38 MAPK pathway in downregulation of AQP1 by Staphylococcus peptidoglycan [157].…”
Section: Transcriptional/translational Regulationmentioning
confidence: 99%
“…Aldosterone seems to contribute to monocrotaline-induced PAH development as its concentration was found to be increased in both plasma and lung homogenates, and spironolactone prevented pulmonary vascular remodeling [ 33 ]. Similar changes have been observed in human PAH [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…COPD is itself a fluid‐retaining state associated with hyperaldosteronism 4,10–12 . The harmful effects of hyperaldosteronism in HFrEF are well recognised and aldosterone may also have detrimental effects in the pulmonary vasculature, which is especially relevant given the propensity of patients with COPD to develop pulmonary hypertension 13–17 …”
Section: Discussionmentioning
confidence: 99%
“…Each condition is associated with an increase in plasma aldosterone concentration and MRAs should help counter fluid retention, block any adverse effects of exogenous corticosteroids at the mineralocorticoid receptor and mitigate the risk of hypokalaemia with beta‐2 agonists 4,10–12 . In addition, MRAs seem to attenuate pathogenic vascular remodelling in the lungs, and right ventricular failure, in experimental models of pulmonary hypertension 13–17 . These problems also occur as secondary complications in some patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation